VISCERAL ADIPOSE TISSUE INFLUENCES ANTI-TUMOR NECROSIS FACTOR (TNF) TREATMENT RESPONSE IN IBD. (21st January 2021) - Gu, Phillip; Chhabra, Avneesh; Chhittajallu, Punya; Chang, Christopher; Mendez, Denisse; Gilman, Andrew; Fudman, David; Xi, Yin; Feagins, Linda
Abstract: Background: Data describing the effect of obesity on anti-TNF treatment response in inflammatory bowel disease (IBD) are conflicting. This likely reflects the shortcomings of using body mass index (BMI) to capture an individual's adipose stores. Recent studies have found visceral adipose tissue (VAT), not BMI, is associated with IBD-related complications and post-operative recurrence. However, the relationship between VAT and treatment response is unclear. We aim to evaluate the effect of VAT on anti-TNF treatment response. Methods: IBD patients starting anti-TNF agents between 1/1/2009 to 7/31/2019 at two academic medical centers were included. Three-dimensional VAT volume was measured from CT scans with Aquarius (iNtuition, Foster City, CA). Patients were categorized by predefined volume cutoffs: <1500cm 3, 1500-2999cm 3, > 3000cm 3 . Primary outcomes included composite endpoint of corticosteroid-free response (CFR) at 6 and 12 months defined by meeting one of the following: a) clinical response based on Harvey Bradshaw Index for Crohn's disease (CD) or Lichtiger score for ulcerative colitis (UC) b) endoscopic improvement based on ulcer healing for CD and Mayo score for UC compared to baseline or c) 50% improvement or normalization of CRP or fecal calprotectin. Secondary outcomes included IBD-related surgery at 6 and 12 months. We performed a multivariable logistic regression on CFR and surgery, adjusting for age, gender, IBD diagnosis, disease duration, active tobacco use, and immunomodulator exposure, to calculate adjusted odds ratio (aOR) and 95% confidence interval (CI). Results: We included 182 patients. Table 1 summarizes differences in baseline characteristics. There were no differences in CFR at 6 months. Compared to those with VAT volume <1500cm 3, patients with VAT volume 1500-2999cm 3 were significantly more likely to achieve CFR at 12 months (aOR 3.27, [95%CI 1.26–8.5]), but not for those with VAT volume > 3000cm 3 (aOR 0.45, [95%CI 0.13–1.50], Figure 1b ). With respect to surgery within 6 months, patients with volume > 3000cm 3 were significantly more likely to undergo surgery than those with VAT volume <1500cm 3 (aOR: 7.99 [95%CI 1.49–2.94]), while there was no significant difference with patients with VAT volume 1500-2999cm 3 (aOR: 0.63 [95%CI 0.14–2.78]). While not statistically significant, a similar trend was observed at 12 months with those with VAT volume >3000cm 3 having the highest risk of surgery (aOR: 3.55 [95%CI 0.87–14.61], Figure 1c and d). Conclusion: In this retrospective, multicenter, cohort study, we found VAT influences treatment response but not in a dose-dependent manner as previously hypothesized. If confirmed by future prospective studies, VAT may be employed as a biomarker to better inform treatment decisions and improve outcomes, especially considering the growth of artificial intelligence in medical imaging.